The Policy of the Government of the Republic of Indonesia in Handling the Status of Citizens of Indonesian Descent in the Southern Philippines - Michael Mamentu; Joyce Jacinta Rares (Universitas Muhammadiyah Gorontalo, 2025)
The migration of the Sangihe and Talaud Islands people to the Southern Philippines, which has been ongoing since the 17th century, has created a large diaspora phenomenon now estimated to exceed 10,000 people. The main problem faced by this community is statelessness, where they are categorized as undocumented citizens vulnerable to discrimination, exploitation, and limited access to basic services. This article aims to analyze the policies of the Government of the Republic of Indonesia in handling the legal status of these descendants. This research uses a descriptive qualitative approach with data collection through in-depth interviews with key informants from the Ministry of Foreign Affairs, the Ministry of Law and Human Rights, and Indonesian representatives in the Philippines (the Indonesian Embassy in Manila and the Indonesian Consulate General in Davao). The results show that in the organizational dimension, the government has established a cross-sectoral institutional structure and bilateral cooperation through the Joint Commission for Bilateral Cooperation (JCBC) forum and collaboration with the UNHCR. In the interpretation dimension, the government translates citizen protection policies through the registration process, genealogical verification, and technical identification of Persons of Indonesian Descent (PIDs) in the field. In the application dimension, concrete steps were implemented through the issuance of Indonesian passports to thousands of verified citizens and the diplomatic granting of special non-immigrant visas. This study concludes that this policy is a manifestation of the state's presence in protecting the human rights of diaspora in border regions.